2021
DOI: 10.2147/ijgm.s304123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Intratympanic Injection of Dexamethasone for Treating Sudden Deafness

Abstract: Introduction A variety of causes may induce sudden deafness. However, it remains challenging to determine the exact cause in a clinic. There is no standard treatment for this disease due to its unclear etiology. Objective The present study aims to investigate the clinical efficacy of the intratympanic injection of dexamethasone for treating sudden deafness. Methods A total of 154 patients with sudden deafness were retrospectively analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…To date, the exact mechanisms of sensorineural hearing loss (HL) are still not completely understood [ 3 ] but in preclinical and clinical otology fields, in vitro and in vivo studies and clinical trials are often conducted to seek pharmacotherapies of inner ear disorders [ 4 , 5 , 6 ]. Among these, inflammation-suppressing substances, such as glucocorticoids, and especially dexamethasone, have been widely tested as a potential therapy to treat inner ear pathologies including sudden sensorineural hearing loss (SSNHL) [ 7 , 8 , 9 , 10 ], Menière’s disease [ 11 , 12 , 13 , 14 ], and acute tinnitus [ 15 ]. Additionally, dexamethasone is intensively investigated for its benefit in cochlear implant (CI) patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the exact mechanisms of sensorineural hearing loss (HL) are still not completely understood [ 3 ] but in preclinical and clinical otology fields, in vitro and in vivo studies and clinical trials are often conducted to seek pharmacotherapies of inner ear disorders [ 4 , 5 , 6 ]. Among these, inflammation-suppressing substances, such as glucocorticoids, and especially dexamethasone, have been widely tested as a potential therapy to treat inner ear pathologies including sudden sensorineural hearing loss (SSNHL) [ 7 , 8 , 9 , 10 ], Menière’s disease [ 11 , 12 , 13 , 14 ], and acute tinnitus [ 15 ]. Additionally, dexamethasone is intensively investigated for its benefit in cochlear implant (CI) patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…If necessary, mecobalamin nutrition is supplemented to protect neural function. [ 14 ] Li et al [ 15 ] found that the treatment effectiveness of injecting corticosteroid drug dexamethasone into the tympanic cavity was better than that of the CG, and the efficacy of injecting dexamethasone into the tympanic membrane was better. Zhang et al [ 16 ] explored the value of coagulation markers in prognostic analysis of patients with SHL.…”
Section: Discussionmentioning
confidence: 99%
“…Although Dex is widely used for the treatment of diseases characterized by hearing loss, including sudden sensorineural hearing loss (SSNHL) [39] and Meniere's disease [64], there are in vivo studies showing that Dex had no effect [65] or that there was remarkable heterogeneity in treatment response across patients with SSNHL [66], and some even reported a toxic effect [38,66]. Moreover, to date, a significant knowledge gap exists relating to the localization of the action of corticosteroids in the inner ear and the cell types involved in their response [66].…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (Dex) is a steroid drug with a strong anti-inflammatory effect on cochlear tissues, capable of significantly reducing hearing loss when applied locally or systemically [38]. Dex has been shown to preserve hearing in guinea pig models of cochlear implantation [39], and at present, intra-tympanic injections of Dex are very effective in treating sudden deafness caused by circulatory disorders [39]. However, some studies highlight the negative side effects of Dex on inner ear tissues, including increased hearing loss [40].…”
Section: Introductionmentioning
confidence: 99%